Pengaruh Economic Value Added (EVA) dan Market Value Added (MVA) Terhadap Kinerja Keuangan PT Mayora Indah Tbk yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2010-2020 - Suhartono, Agus (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to determine the influence of Economic Value Added (EVA) and Market Value Added (MVA) on stock prices. The research was conducted on PT Mayora Indah Tbk, a company listed on the Indonesia Stock Exchange (IDX), covering the period from 2010 to 2020. This study employs a quantitative research approach, relying on financial data from annual reports. The object of the research is PT Mayora Indah Tbk, which is publicly traded on the Indonesia Stock Exchange (IDX) during the specified period. The data analysis methods used include descriptive statistical analysis, classical assumption tests, simple linear regression analysis, and multiple linear regression analysis. Based on the analysis results, Economic Value Added (EVA) does not have a significant influence on stock prices, leading to the rejection of H1. In contrast, Market Value Added (MVA) has a significant impact on stock prices, supporting the acceptance of H2. Furthermore, simultaneous testing (F-test) indicates that both EVA and MVA collectively influence stock prices. The coefficient of determination (R²) analysis shows that these variables account for a substantial portion of the variation in stock prices, while the remaining influence is attributed to other factors.